The Educational Encoding Style in the Plays of Ahmed Kamel - Ikhlas Abdul Qadir Taher Hussein ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2026)
Despite the importance of style in generating and shaping meaning in theatrical works, and in influencing how performances are received and interpreted by school students, issues related to its significance and function have often received insufficient scholarly attention. School theatre, however, represents an important medium for conveying artistic and intellectual messages to young audiences.Accordingly, this study investigates educational encoding in the plays of Ahmed Kamel that were presented to pupils in schools affiliated with the Third Rusafa Directorate of Education in Baghdad between 2014 and 2024.To achieve this aim, the researcher adopted the descriptive–analytical method. The theoretical framework of the study consists of two sections: the first addresses the concept of style, while the second examines educational encoding in Ahmed Kamel’s theatrical works. Based on indicators derived from the theoretical framework, an analytical table consisting of specific criteria was developed to identify the functions and meanings of the educational codes. This table was employed as a research instrument for analyzing the selected sample, namely the play Fatin’s Journey in the City of Rules.The findings indicate that the play deviates from a conventional dramatic plot. Instead, the events follow a linear structure unified by a single central idea, with dramatic conflict among the characters shaping the narrative. Through this structure, the play presents a series of situations inspired by the nature and grammatical rules of the Arabic language. These elements were carefully selected to facilitate students’ learning of the parts of speech in Arabic, including nouns, verbs of various types, and particles.The characters in the play possess equal dramatic significance. Although the play includes both principal and secondary characters, each performs a specific role related to the Arabic language. The text also incorporates several educational codes, including self-affirmation, critical thinking, participation in problem-solving, inductive reasoning, constructive dialogue, and questioning.The findings lead to the following conclusions:The playwright employs educational encoding to encourage thinking, questioning, self-affirmation, and understanding one’s role in the learning process, while also promoting effective delivery techniques and correct pronunciation. These elements contribute to shaping the child’s personality during the basic stages of education.The play also incorporates songs and poetic passages performed by the characters, combining educational and moral dimensions while enhancing the entertaining aspect of the theatrical performance.The study therefore recommends increasing the attention of educators and children’s playwrights to educational theatre that emphasizes the theatricalization of curricula, promotes cultural awareness, and conveys noble values through symbolic educational encoding, given its positive influence on students.DOI: https://doi.org/10.54633/2333-024-057-013